No magnesium is needed for binding of the stimulator of interferon genes to cyclic dinucleotides. Issue 9 (2nd September 2019) - Smola, Miroslav; Birkus, Gabriel; Boura, Evzen
Abstract : Stimulator of interferon genes (STING) is a key component of innate intracellular immunity. It is activated by the binding of cyclic dinucleotides (CDNs) produced by cyclic GMP‐AMP synthase or of bacterial origin. The interactions of CDNs with STING are well understood; however, contrary to the previously published structure, it is shown that no Mg atoms are present in the binding site of STING. Abstract : Stimulator of interferon genes (STING) binds cyclic dinucleotides (CDNs), which induce a large conformational change of the protein. The structural basis of activation of STING by CDNs is rather well understood. Unliganded STING forms an open dimer that undergoes a large conformational change (∼10 Å) to a closed conformation upon the binding of a CDN molecule. This event activates downstream effectors of STING and subsequently leads to activation of the type 1 interferon response. However, a previously solved structure of STING with 3′, 3′‐c‐di‐GMP shows Mg atoms mediating the interaction of STING with this CDN. Here, it is shown that no Mg atoms are needed for this interaction; in fact, magnesium can in some cases obstruct the binding of a CDN to STING.